Aplikasi Data Pencari Kerja Dalam Bursa Kerja Khusus - Dimas Rizky Wardana; Indra Kanedi; Ricky Zulfiandry (UNIVED Press, 2023)
Abstract-Computers are a set of technologies that really help human work. Application is a computer application that is intended to help solve problems in a specific field, this system works by using job knowledge which is the most important thing because it has a direct effect on a person's survival. Data Applications for Job Seekers in the Special Job Exchange, System design is the stage where the author will design the application to be built. This stage is the stage where the author will go through planning flowchart designs, data flow diagrams, input display designs and output display designs. Based on the research results, the following conclusions can be drawn, the implementation of the Bengkulu City 1 State Vocational High School Special Job Exchange can run smoothly, the purpose of the Bengkulu City 1 State Vocational High School Special Job Exchange in increasing student competence and helping the distribution of graduates can be successful by Good. By having competencies that are in accordance with the needs of the world of work, graduates of the Bengkulu City 1 State Vocational High School can easily be accepted into the world of work. This is evidenced by the search results for graduates of the Bengkulu City 1 State Vocational High School which shows that graduates of the Bengkulu City 1 State Vocational High School easily and quickly get jobs.